Effects in the solubility of CaCO3: Experimental study and model description - Coto, B.; Martos, C.; Peña, J.L.; Rodríguez, R.; Pastor, G. (Fluid phase equilibria, 2012)
► ELEC-NRTL is a powerful thermodynamic model for concentrated electrolyte solutions. ► Simulation proposed scheme is flexible enough to reproduce a wide range of conditions. ► pH and CO2 pressure are main variables involved in CaCO3 solubility equilibria. ► Apparently different experimental data can be compared through calculated values. Crude oil is usually co-produced with reservoir water, with increasing content in the production fluid along field life. Changes in temperature, pressure, and/or chemical composition may cause significant precipitation of inorganic salts (“scales”) during production. Therefore, the knowledge of the influence that different variables may have on salt solubility is critical to anticipate or identify potential flow assurance problems related to scales. The present work is specifically focused in the study of calcium carbonate precipitate formation as a main component of “scales”. Due to the number of variables involved in calcium carbonate precipitation (temperature, pressure, CO2 partial pressure, other salt content) and the heterogeneity of reservoir conditions, there are serious limitations to perform a full experimental study covering all the possible precipitation scenarios. Solubility data presented in this work, both previously reported and experimentally determined, cover a wide range of experimental conditions. A simulation model that allows quantitative predictions in different scenarios is an interesting tool. A versatile simulation algorithm was developed using ASPEN PLUS® 7.1 from Aspen Technology, Inc., that allows different experimental conditions and the quantification of the influence of temperature, pressure and pH in CaCO3 solubility. This simulation scheme was applied to describe both literature and new experimental solubility data. Predicted results were in reasonable agreement with experimental information. The solubility of calcium carbonate decreases with temperature, increases with pressure and shows a maximum in presence of NaCl. The CO2 partial pressure has strong effect because it is direct relation with solution pH that modify the amount of ionic species present in the aqueous solution, and hence increasing the solubility of calcium carbonate. Special attention was devoted to such pH effect but, in order to have a fully predictive model, no parameters fit was carried out. The main conclusion of this work is the suitable simulation scheme to describe and predict the solubility of calcium carbonate at different conditions.